The Extent of Practicing Knowledge Management in UNRWA Schools in Jordan from the Point of View of Principals - Subhi Al-Thaher; Khalid Al-Sarhan (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the degree of practice of knowledge management processes (knowledge diagnosis, knowledge generation, knowledge organization, knowledge storage and perpetuation, knowledge retrieval, knowledge sharing, and knowledge application) in the schools of the United Nations Agency (UNRWA) in Jordan from the point of view of their principals. To achieve this goal, a descriptive survey method was used. The study population consisted of all the principals of the United Nations Agency (UNRWA) schools in Jordan for the academic year 2014/2015 (n=174). A study tool (a questionnaire) was developed, which consisted of (61) items distributed on seven domains. The results of the study showed that the degree of practicing knowledge management processes in the schools of the United Nations Agency (UNRWA) in Jordan from the point of view of its principals came to a medium degree. The results also showed that there were statistically significant differences attributed to the variable years of experience on some domains of the study in favor of school principals who had experience (10 years or more). Other results are highlighted in the paper. The study recommends paying attention to knowledge management as a modern administrative method that is consistent with the trends of the era of knowledge, and granting UNRWA school principals administrative powers that enable them to practice knowledge management processes effectively.